2015
DOI: 10.4209/aaqr.2014.02.0029
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Characteristics of Aerosol Black Carbon in Relation to Long Range Transport over Tripura in Northeast India

Abstract: This study presents the characteristics of aerosol black carbon (BC) from a rural continental site, Agartala, located in the North-Eastern part of India using two year measurements from September 2010 to September 2012. Diurnal and seasonal variations are examined in relation to the unique geographical location, changeable meteorological conditions and distinct source characteristics. Winter season is characterized by extremely high BC concentration (17.8 ± 9.2 µg/m 3 ) comparable to those seen in urban enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(9 citation statements)
references
References 62 publications
1
7
0
Order By: Relevance
“…Seasonal average concentration of BC and LAOC corresponded with the changes observed in the aerosol load; respectively they were (BC and LAOC) 2.2 µg m -3 and 1.5 µg m -3 (summer), 1.6 µg m -3 and 1.2 µg m -3 (monsoon) and 2.8 µg m -3 and 2.9 µg m -3 (winter). The seasonal profile of BC was comparable with other investigations from India (Tiwari et al, 2014;Guha et al, 2015).…”
Section: Temporal Profile Of Pm 25 Bc and Laocsupporting
confidence: 77%
“…Seasonal average concentration of BC and LAOC corresponded with the changes observed in the aerosol load; respectively they were (BC and LAOC) 2.2 µg m -3 and 1.5 µg m -3 (summer), 1.6 µg m -3 and 1.2 µg m -3 (monsoon) and 2.8 µg m -3 and 2.9 µg m -3 (winter). The seasonal profile of BC was comparable with other investigations from India (Tiwari et al, 2014;Guha et al, 2015).…”
Section: Temporal Profile Of Pm 25 Bc and Laocsupporting
confidence: 77%
“…The stepwise evolution of the Asian summer monsoon begins in spring and contributes a significant amount of rainfall to the total annual precipitation over China (25 %-40 %) and over South Asia (∼ 11 %-20 %) due to deep convection over the Bay of Bengal, Tibetan Plateau, and South China Sea (Guhathakurta and Rajeevan, 2008;Li et al, 2016). The distribution of OLR from NCEP Reanalysis data during the spring season confirms that deep convection occurs over the maritime continent that extends to the South China Sea, Bay of Bengal, Malay Peninsula, and Indonesia (Fig.…”
Section: Transport Of Biomass Burning Aerosol Into the Upper Troposphere And Lower Stratospherementioning
confidence: 99%
“…To assess the regional and global climate change, a detailed study of spatiotemporal distribution of BC concentration is required; BC being inert with around five days of residence time can be transported over long distances [13]. Although several studies have been carried out in different cities around the world (including Beijing [14], Lahore [15] and, in India, Delhi [16], Trivandrum [17], Ahmedabad [18], Pune [19], Vishakhaptnam [20], and Agartala [21]), few studies are available for the eastern-central plain region of the country such as Nagpur [22]. In most of the studies, BC mass concentration has been reported to be the highest in winter season, particularly in December.…”
mentioning
confidence: 99%